3-D Microwave Imaging for Breast Cancer - Cheng, George; Zhu, Yong; Grzesik, Jan (Společnost pro radioelektronické inženýrství, 2012)
We introduce a novel microwave imaging technique for breast cancer detection. Our approach provides a one-pass inverse image solution, which is completely new and unprecedented, unrelated to tomography or radar-based algorithms, and unburdened by the optimization toil which lies at the heart of numerical schemes. It operates effectively at a single frequency, without requiring the bandwidth of radar techniques. Underlying this new method is our unique Field Mapping Algorithm (FMA), which transforms electromagnetic fields acquired upon one surface, be it through outright measurement or some auxiliary computation, into those upon another in an exact sense.
Keywords: Electromagnetic waves; imaging; inverse scattering